2011
DOI: 10.1177/09596518jsce1037
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectrically actuated hydraulic valve design for high bandwidth and flow performance

Abstract: The performance of hydraulically actuated machine systems could be improved with the use of valves that have high bandwidth and high flowrates under low pressure drops. Although high flowrates can be achieved using very large spool strokes and/or diameters, the overall bandwidth of the valve will be reduced. Research has therefore been undertaken on a prototype valve design incorporating the Horbiger plate principle, which utilizes multiple metering edges to allow high flowrates to be obtained at low pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…The experimental tests were conducted on two different rig structures with the FBN cancellation valve in series and bypass configurations. A novel piezoelectric valve was used as the actuator to produce the anti-noise in the system because it had a fast response and high bandwidth [16]. A PI E-481 highpower piezo-amplifier was used to drive the piezoelectric actuator.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The experimental tests were conducted on two different rig structures with the FBN cancellation valve in series and bypass configurations. A novel piezoelectric valve was used as the actuator to produce the anti-noise in the system because it had a fast response and high bandwidth [16]. A PI E-481 highpower piezo-amplifier was used to drive the piezoelectric actuator.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Uusitalo et al (2010) developed a static 2-D axisymmetric finite element model for an electromagnetic domain of a novel bistable hammer type digital valve to evaluate electromagnetic force. It was found that the simulated model accurately predicted power consumption values but failed to capture the accurate response time; Wilfong (2011) and Branson et al (2011) both developed the static computational fluid dynamics (CFD) models for the flow domains of their high speed valve systems to acquire flow force profiles at different valve positions. However, this approach does not include the dynamic of the valve poppet/spool, which causes modelling discrepancies with the actual valve performances.…”
Section: Introductionmentioning
confidence: 98%
“…The response time of this valve ranged from 2 to 8ms. Branson et al (2011) developed a piezo-electrically actuated valve utilizing the Horbiger plate principle and achieved less than a 1.5 ms on/off switching time but only 20L/min nominal flow @ 5bar pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a promising research field aims to replace the electromagnetic torque motor assembly with piezoelectric actuators, thus reducing complexity and manufacturing costs [2]. Different types of piezoelectric actuators have been used to directly drive the main stage spool or to drive the flapper, jet pipe or deflector jet in the pilot stage [11][12][13][14][15][16][17][18][19][20][21], showing that the idea of using a piezo-electric actuator to drive a servovalve is feasible and promising. One of the commercially available piezoelectric actuators that has been used for this purpose is the stack-type, in which several piezo elements are joined together to form a multi-layer actuator [11][12][13]; in parallel to piezo-stacks actuators, also amplified piezo-stack actuators, which can provide higher displacement but lower forces, have been proposed to replace the torque motors in servovalves [14][15][16].…”
Section: Introductionmentioning
confidence: 99%